Tri-ortho-cresyl phosphate induces autophagy of mouse ovarian granulosa cells. Issue 1 (July 2019) - Wang, Jinglei; Ruan, Wenli; Huang, Boshu; Shao, Shuxin; Yang, Dan; Liu, Mengling; Zeng, Lin; Wei, Jie; Chen, Jiaxiang
Abstract : Tri-ortho-cresyl phosphate (TOCP) has been widely used as plasticizers, plastic softeners and flame-retardants in industry and reported to have male reproductive toxicology. However, it is still unknown whether TOCP affects the female reproductive system and its underlying mechanism. In the present study, we found that TOCP exposure significantly decreased ovarian coefficient, caused disintegration and depletion of the granulosa cells in the ovary tissue and significantly inhibited the level of serum estradiol (E2). TOCP markedly increased both LC3-II and the ratio of LC3-II/LC3-I as well as autophagy proteins ATG5 and Beclin1 in the ovary tissue, implying that TOCP could induce autophagy in the ovary tissue. To further investigate the potential mechanism, primary ovarian granulosa cells were isolated in vitro and treated with 0–0.5 mM TOCP for 48 h. We showed that TOCP decreased the number of viable mouse granulosa cells without affecting cell cycle and apoptosis of the cells. Intriguingly, TOCP treatment markedly increased both LC3-II and the ratio of LC3-II/LC3-I as well as ATG5 and Beclin1. Furthermore, transmission electron microscopy (TEM) showed that autophagic vesicles in the cytoplasm increased significantly in the TOCP-treated cells, indicating that TOCP could induce autophagy in the cells. Taken together, TOCP reduces the number of viable cells and induces autophagy in mouse ovarian granulosa cells without affecting cell cycle and apoptosis.